Copper-Catalyzed N-Arylation of Sulfonamides with Boronic Acids in Water under Ligand-Free and Aerobic Conditions - Nasrollahzadeh, Mahmoud; Ehsani, Ali; Maham, Mehdi (Synlett, 2014)
An efficient and novel method for the copper-catalyzed arylation of sulfonamides in water under ligand-free conditions is reported. The significant advantages of this methodology are high yields, simple workup procedure, and elimination of toxic materials.
Keywords: arylation; arylboronic acid; ligand-free; copper; sulfonamide; water